Respiratory viruses detected in Mexican children younger than 5 years old with community-acquired pneumonia: a national multicenter study - Wong Chew, Rosa María; García León, Miguel L.; Noyola, Daniel E.; Pérez González, Luis Felipe; Gaitán Meza, Jesús; Vilaseñor Sierra, Alberto; Martínez Aguilar, Gerardo; Rivera Núñez, Víctor Hugo; Newton Sánchez, Oscar A.; Firo Reyes, Verónica; Del Río Almendarez, Carlos N.; González Rodríguez, Alejandra Pamela; et al. (2017)
Background: Acute respiratory infections are the leading cause of mortality in children worldwide, especially in developing countries. Pneumonia accounts for 16% of all deaths of children under 5 years of age and was the cause of death of 935 000 children in 2015. Despite its frequency and severity, information regarding its etiology is limited. The aim of this study was to identify respiratory viruses associated with community-acquired pneumonia (CAP) in children younger than 5 years old. Methods: One thousand four hundred and four children younger than 5 years of age with a clinical and/or radiological diagnosis of CAP in 11 hospitals in Mexico were included. Nasal washes were collected, placed in viral medium, and frozen at 70 C until processing. The first 832 samples were processed using the multiplex Bio-Plex/Luminex system and the remaining 572 samples using the Anyplex multiplex RT-PCR. Clinical data regarding diagnosis, clinical signs and symptoms, radiographic pattern, and risk factors were obtained and recorded. Results: Of the samples tested, 81.6% were positive for viruses. Respiratory syncytial virus (types A and B) was found in 23.7%, human enterovirus/rhinovirus in 16.6%, metapneumovirus in 5.7%, parainfluenza virus (types 1–4) in 5.5%, influenza virus (types A and B) in 3.6%, adenovirus in 2.2%, coronavirus (NL63, OC43, 229E, and HKU1) in 2.2%, and bocavirus in 0.4%. Co-infection with two or more viruses was present in 22.1%; 18.4% of the samples were negative. Using biomass for cooking, daycare attendance, absence of breastfeeding, and co-infections were found to be statistically significant risk factors for the presence of severe pneumonia. Conclusions: Respiratory syncytial virus (types A and B), human enterovirus/rhinovirus, and metapneumovirus were the respiratory viruses identified most frequently in children younger than 5 years old with CAP. Co-infection was present in an important proportion of the children.